2012
DOI: 10.4236/ojanes.2012.25045
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Resuscitation in the Prone Position

Abstract: Cardiac arrest in unusual positions represents an additional challenge for anesthesiologists. This paper reports a successful cardiopulmonary resuscitation during neurosurgical procedure in which high-quality chest compressions was performed in the prone position. The aim of this report is disclose the knowledge of resuscitation maneuvers in a position other than supine. A 77-year-old female patient presented for excision of parietal-occipital meningioma in the prone position with the head fixed on a Mayfield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Survival to hospital discharge with favourable neurological outcome was not explicitly reported in any adult or paediatric case. There were implicit reports of survival to hospital discharge with favourable neurological outcome in eight adult cases (‘without neurologic deficit’ 21 ; ‘no cerebral injury’ 20 ; ‘recovered uneventfully’ 23 ; ‘without deficits’ 33 ; ‘awake and well oriented at 7 days’ 22 ; ‘without sequelae’ 24 ; ‘could carry out simple tasks’ 25 ; and ‘discharged from hospital in a stable neurological condition’ 30 ) and seven paediatric cases (‘no evidence of significant cerebral dysfunction’ 38 ; ‘returned to baseline over two weeks’ 39 ; ‘recovered without sequelae’ 40 ; ‘no adverse neurological sequelae’ 41 ; ‘in good condition’ 47 ; ‘made an uneventful recovery’ 29 ; and ‘unchanged from preoperative status’ 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…Survival to hospital discharge with favourable neurological outcome was not explicitly reported in any adult or paediatric case. There were implicit reports of survival to hospital discharge with favourable neurological outcome in eight adult cases (‘without neurologic deficit’ 21 ; ‘no cerebral injury’ 20 ; ‘recovered uneventfully’ 23 ; ‘without deficits’ 33 ; ‘awake and well oriented at 7 days’ 22 ; ‘without sequelae’ 24 ; ‘could carry out simple tasks’ 25 ; and ‘discharged from hospital in a stable neurological condition’ 30 ) and seven paediatric cases (‘no evidence of significant cerebral dysfunction’ 38 ; ‘returned to baseline over two weeks’ 39 ; ‘recovered without sequelae’ 40 ; ‘no adverse neurological sequelae’ 41 ; ‘in good condition’ 47 ; ‘made an uneventful recovery’ 29 ; and ‘unchanged from preoperative status’ 42 ).…”
Section: Resultsmentioning
confidence: 99%
“… 22 Gomes and Bersot reported successful prone CPR in a neurosurgical patient, using compression over the mid-thoracic level, but no sternal counter-pressure. 44 Kwon et al reviewed 100 chest CTs to determine where to compress the largest left ventricular mass. Once again, it was mid-thoracic, below the inferior angle of the scapulae.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Gomes et al reported successful prone CPR in a neurosurgical patient, using compression over the mid-thoracic level, but no sternal counter-pressure. [44] Kwon et al reviewed 100 chest CTs to determine where to compress the largest left ventricular mass. Once again, it was mid-thoracic, below the inferior angle of the scapulae.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Dequin et al reported successful prone CPR in an ICU patient, in which they used two-handed mid-thoracic compression and a second person for sternal counter-pressure [22]. Gomes et al reported successful prone CPR in a neurosurgical patient, using compression over the mid-thoracic level, but no sternal counter-pressure [44]. Kwon et al reviewed 100 chest CTs to determine where to compress the largest left ventricular mass.…”
mentioning
confidence: 99%